Bone-mineral density and other features of the female athlete triad in elite endurance runners: A longitudinal and cross-sectional observational study - Pollock, N.; Grogan, C.; Perry, M.; Pedlar, C.; Cooke, K.; Morrissey, D.; Dimitriou, L. (International Journal of Sport Nutrition and Exercise Metabolism, 2010)
Low bone-mineral density (BMD) is associated with menstrual dysfunction and negative energy balance in the female athlete triad. This study determines BMD in elite female endurance runners and the associations between BMD, menstrual status, disordered eating, and training volume. Forty-four elite endurance runners participated in the cross-sectional study, and 7 provided longitudinal data. Low BMD was noted in 34.2% of the athletes at the lumbar spine, and osteoporosis in 33% at the radius. In cross-sectional analysis, there were no significant relationships between BMD and the possible associations. Menstrual dysfunction, disordered eating, and low BMD were coexistent in 15.9% of athletes. Longitudinal analysis identified a positive association between the BMD reduction at the lumbar spine and training volume (p = .026). This study confirms the presence of aspects of the female athlete triad in elite female endurance athletes and notes a substantial prevalence of low BMD and osteoporosis. Normal menstrual status was not significantly associated with normal BMD, and it is the authors` practice that all elite female endurance athletes undergo dual-X-ray absorptiometry screening. The association between increased training volume, trend for menstrual dysfunction, and increased loss of lumbar BMD may support the concept that negative energy balance contributes to bone loss in athletes.